2012
DOI: 10.1103/physrevd.86.023511
|View full text |Cite
|
Sign up to set email alerts
|

More on QCD ghost dark energy

Abstract: The difference between vacuum energy of quantum fields in Minkowski space and in Friedmann-Robterson-Walker universe might be related to the observed dark energy. The vacuum energy of the Veneziano ghost field introduced to solve the U (1) A problem in QCD is of the form, H + O(H 2 ). Based on this, we study the dynamical evolution of a phenomenological dark energy model whose energy density is of the form αH + βH 2 . In this model, the universe approaches to a de Sitter phase at late times. We fit the model w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 99 publications
8
87
0
1
Order By: Relevance
“…Thus the f (R, T ) ghost model is not stable in this scenario which is in accordance with the results in (Cai et al 2011). We also test the evolution of squared speed of sound for stability analysis of ghost f (R, T ) model.…”
Section: Stability Of Ghost R + F (T ) Modelsupporting
confidence: 72%
See 1 more Smart Citation
“…Thus the f (R, T ) ghost model is not stable in this scenario which is in accordance with the results in (Cai et al 2011). We also test the evolution of squared speed of sound for stability analysis of ghost f (R, T ) model.…”
Section: Stability Of Ghost R + F (T ) Modelsupporting
confidence: 72%
“…Therefore, GDE helps to get rid of fine tuning and coincidence problems (Urban and Zhitnitsky 2009; Ohta 2011). Cai et al (2011) fitted this model and developed the constraints on model parameters using the recent observational data SNeIa, CMB, BAO, BNN and the Hubble parameter data.…”
Section: Introductionmentioning
confidence: 99%
“…It was argued that the vacuum energy of the ghost field can be written as H þ OðH 2 Þ, where the sub-leading term H 2 in the GDE model might play a crucial role in the early stage of the universe evolution, acting as the early DE [15]. It was shown [15,16] that taking the second term into account can give better agreement with observational data compared to the usual GDE. The density of this generalized ghost dark energy (GGDE) reads [15] …”
Section: Introductionmentioning
confidence: 49%
“…[13] discussed that the contribution of the Veneziano QCD ghost field to the vacuum energy is not exactly of order H and a sub-leading term H 2 appears due to the fact that the vacuum expectation value of the energy-momentum tensor is conserved in isolation [14]. It was argued that the vacuum energy of the ghost field can be written as H þ OðH 2 Þ, where the sub-leading term H 2 in the GDE model might play a crucial role in the early stage of the universe evolution, acting as the early DE [15]. It was shown [15,16] that taking the second term into account can give better agreement with observational data compared to the usual GDE.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al (2012) suggested that the contribution of subleading term (i.e., H 2 ) in the ordinary ghost DE can be helpful in describing the early evolution of the universe. He proposed the so called generalized ghost DE density…”
Section: Equation Of State Parametermentioning
confidence: 99%